Nevus of Ota: The Unusual Birthmarks: A Case Report - Begum, Tamanna; Rai, Punam; Kaur, Gursharan; Islam, Rafiqul; Kadir, Sadika (Bangladesh Journal of Child Health, 2020)
Nevus of Ota is a benign congenital melanosis bulbi. It is a rare entity, commonly seen in female. It occurs among Asians and Africans. It mainly involves the eye, skin and ear. It is predominantly unilateral but could be bilateral. Typical clinical manifestation was present in our case, however, biopsy is the investigation of choice. There is no specific treatment but ophthalmological and dermatological intervention can be opted. Outcome is remarkably good. Here we reported a case of a child with Nevus of Ota who was primarily admitted at paediatric department with enteric fever. We managed her conservatively and followed up in specific department. Bangladesh J Child Health 2020; VOL 44 (1) :60-63